Mandibular incisor extraction treatment in Angle's Class I malocclusion with peg-shaped maxillary lateral incisors - Ankit H Shah; Darshit H Shah (Wolters Kluwer Medknow Publications, 2016)
Accurate diagnosis and treatment planning are essential for obtaining ideal treatment result in cases involving mandibular incisor extraction. This case report describes a 15-year-old female with balanced soft-tissue profile, peg-shaped maxillary lateral incisors, and moderate mandibular anterior crowding treated with a mandibular incisor extraction. Ideal overbite and overjet were achieved. "Black triangle" formation was avoided due to the bodily movement of mandibular incisors and the use of uprighting springs for ideal axial inclination of mandibular incisors. A mandibular incisor extraction can be an effective treatment option in carefully selected clinical situations.